2020
DOI: 10.1101/2020.12.15.422931
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A diencephalic circuit for opioid analgesia but not positive reinforcement

Abstract: Mu opioid receptor (MOR) agonists are the most effective analgesics, but their use risks respiratory depression and addiction. The epithalamic lateral habenula (LHb) is a critical site that signals aversive states, often via indirect inhibition of reward circuitry, and MORs are highly expressed in the LHb. We found that the LHb is a potent site for MOR-agonist analgesia. Strikingly, LHb MOR activation generates negative reinforcement but is not rewarding in the absence of noxious input. While the LHb receives … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 66 publications
(130 reference statements)
0
2
0
Order By: Relevance
“…While opioids affect multiple sites in pain pathways, as well as reward pathways, in the brain [63][64][65] , we found that buprenorphine, a partial µ-opioid agonist/k-opioid antagonist, dramatically decreased inhibitory responses to an aversive stimulus in dopamine neurons but it did not affect their glutamate inputs. µ-opioid receptor expression is enriched in the RMTg and its direct and indirect upstream inputs such as the parabrachial nucleus (PBN), lHb, and the lateral preoptic area of the hypothalamus (LPO) 21,[32][33][34]66 , and µ-opioid receptor activation inhibits signaling of these neurons [51][52][53][54] . Thus, it is highly probable that opioids preferentially decrease inhibitory input to dopamine neurons and tip the excitatory-inhibitory balance of inputs to dopamine neurons towards excitation (Figure 8F).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While opioids affect multiple sites in pain pathways, as well as reward pathways, in the brain [63][64][65] , we found that buprenorphine, a partial µ-opioid agonist/k-opioid antagonist, dramatically decreased inhibitory responses to an aversive stimulus in dopamine neurons but it did not affect their glutamate inputs. µ-opioid receptor expression is enriched in the RMTg and its direct and indirect upstream inputs such as the parabrachial nucleus (PBN), lHb, and the lateral preoptic area of the hypothalamus (LPO) 21,[32][33][34]66 , and µ-opioid receptor activation inhibits signaling of these neurons [51][52][53][54] . Thus, it is highly probable that opioids preferentially decrease inhibitory input to dopamine neurons and tip the excitatory-inhibitory balance of inputs to dopamine neurons towards excitation (Figure 8F).…”
Section: Discussionmentioning
confidence: 99%
“…If both glutamate inputs and GABA inputs are excited by aversive stimuli, and thus compete each other to shape dopamine responses, the dopamine responses to aversive stimuli may be flexibly altered by slight modulations in the relative strength of excitatory and inhibitory inputs, depending on an animal's state or context (Figure 7G). We focus here on one state alteration: the exogenous administration of opioids, common and effective analgesics which lead to an increase in dopamine excitability and inhibit some direct and indirect inputs to dopamine neurons [47][48][49][50][51][52][53][54] .…”
Section: Opioids May Flip Dopamine Responses To Aversive Stimuli From...mentioning
confidence: 99%